2016
DOI: 10.1152/ajpheart.00044.2016
|View full text |Cite
|
Sign up to set email alerts
|

Twinkle overexpression prevents cardiac rupture after myocardial infarction by alleviating impaired mitochondrial biogenesis

Abstract: Inoue T, Ikeda M, Ide T, Fujino T, Matsuo Y, Arai S, Saku K, Sunagawa K. Twinkle overexpression prevents cardiac rupture after myocardial infarction by alleviating impaired mitochondrial biogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…The decrease in mitochondrial biogenesis is a key component of the development of heart failure after MI [41]. It has been reported that mitochondrial biogenesis was severely impaired in MI and that the preservation of mtDNA copy number alleviated impaired mitochondrial biogenesis [42]. Our results showed that NBP-treatment could protect mitochondrial function in H9c2 cells exposed to oxidative stress.…”
Section: Discussionsupporting
confidence: 55%
“…The decrease in mitochondrial biogenesis is a key component of the development of heart failure after MI [41]. It has been reported that mitochondrial biogenesis was severely impaired in MI and that the preservation of mtDNA copy number alleviated impaired mitochondrial biogenesis [42]. Our results showed that NBP-treatment could protect mitochondrial function in H9c2 cells exposed to oxidative stress.…”
Section: Discussionsupporting
confidence: 55%
“…Earlier studies have demonstrated that helicase overexpression increases mtDNA copy number ( 19 , 22 ) and provides beneficial effects in various pathological conditions ( 25–27 , 55 ). The latter may relate directly to the complex structure of human mtDNA found in heart muscle, in which a substantial fraction is found as catenated multimers that accumulate with age ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the current reporting of echocardiographic results, we accessed PubMed on July 21, 2017, and searched for “mouse and American Journal of Physiology and (echocardiography or echocardiographic or ultrasound).” This search resulted in 437 articles, of which 52 articles were published between January 1, 2016, and present as well as 14 articles that were excluded as false positives (two kidney, one liver, one lung, one bone, one RV, two rat not mouse, one fetal not adult, and five with no cardiac echocardiography results). The remaining 38 articles were analyzed both for completeness of information provided and for quality assessment of the echocardiography values reported ( 11 , 13 , 22 , 27 , 30 , 36 , 38 , 39 , 42 , 45 , 52 , 54 , 57 , 59 , 65 , 70 , 75 , 76 , 78 , 85 , 102 , 114 , 117 119 , 132 , 147 , 148 , 158 , 160 , 165 , 170 , 172 , 182 , 187 , 193 , 201 , 206 ).…”
Section: Echocardiographymentioning
confidence: 99%